Pengaruh Karakteristik Sumber Daya Insani Dan Kepuasan Kompensasi Terhadap Kinerja Karyawan Pada Bank Jatim Syariah Cabang Surabaya. - Wirsayudi, Mohammad Yahya; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2019)
The purpose this research is to find out the influenceshuman resource characteristics and compensation satisfaction on employee performance. The data used in this study are primary data obtained from the questionnaire distributed to employees of the Bank Jatim Syariah Surabaya branch. From the results of the research conducted, it shows that, the influence of human resources characteristic variables on employee performance, the influence of compensation on employee performance, the influence of human resources characteristics and compensation for the performance of employees of the Surabaya Branch of Jatim Syariah.